C50 carotenoids extracted from Haloterrigena thermotolerans strain K15: antioxidant potential and identification - Kesbiç, Fevziye Işıl; Gültepe, Nejdet (Springer Science and Business Media LLC, 2021)
Halophilic archaea are one of the microorganism groups that have adapted to living in high saline environments and are important in terms of their potential use in biotechnology industry. One of the most important compounds they have, carotenoid, is used in food, cosmetics, and medical industries. The selected strain was identified as an extremely halophilic and thermophilic archaeon, Haloterrigena thermotolerans K15, based on morphological, biochemical, and physiological evidence as well as 16S rRNA analysis and screened by a scanning electron microscope and an atomic force microscope for the first time. The carotenoid contents of H. thermotolerans K15 isolated from Salt Lake (Tuz Gölü, Turkey) were determined by RP-HPLC-DAD and their isomers were characterized according to UV-Vis spectra by cis peak intensity and spectral fine structure. In addition to all-trans bacterioruberin as a major carotenoid, many isomers of the bacterioruberin such as monoanhydrobacterioruberin and bisanhydrobacterioruberin were also found. The antioxidant activity of carotenoid extract from H. thermotolerans was analyzed by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging method. The carotenoid extract showed antioxidant activity statistically significantly higher than ascorbic acid and butylated hydroxytoluene as reference compounds (p < 0.05). This is the first study about carotenoid characterization and antioxidant activity of H. thermotolerans K15. The obtained results suggest the potential use of H. thermotolerans K15 products as a substitute for synthesized chemical carotenoids and antioxidants.
Keywords: Halobacteriaceae; RNA, Ribosomal, 16S; Carotenoids; Antioxidants